Pedro A. Sanchez (1940–2026), a social soil scientist - Meine van Noordwijk; Generose Nziguheba; Thomas P. Tomich; Mary Scholes; Fahmuddin Agus; Leigh Winowiecki; Joyce Kasyoki; Peter A. Minang (Proceedings of the National Academy of Sciences, 2026)
Cuban-born Pedro A. Sanchez (1940-2026) became the face of tropical soil science at Cornell University and the North Carolina State University. His combination of process-based understanding of soils, emphasis on farmer choices and conducive policy environments earned him the 2022 World Food prize. After leadership roles in international agroforestry research in Kenya, he returned to academia at Columbia University and the University of Florida, and as a member of the U.S. National Academy of Sciences.